2014
DOI: 10.1089/dna.2013.2248
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of All Nonsynonymous Single-Nucleotide Polymorphisms in the Gene Encoding Human Deoxyribonuclease I-Like 1, Possibly Implicated in the Blocking of Endocytosis-Mediated Foreign Gene Transfer

Abstract: Many nonsynonymous single-nucleotide polymorphisms (SNPs) in the human deoxyribonuclease I-like 1 (DNase 1L1) gene, possibly implicated in the blocking of endocytosis-mediated foreign gene transfer, have been identified, but only limited population data are available and no studies have evaluated whether such SNPs are functional. Genotyping of all 21 nonsynonymous human DNase 1L1 SNPs was performed in 16 different populations representing three ethnic groups using the PCR-restriction fragment length polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…However, all of these functional variants resulting in loss of function, except for SNP p.Arg107Gly with a MAF of 0.004, exhibit a remarkably low distribution (Table 2), similar to that of the CNVs. Thus, it is plausible to assume that DNASE1 has been well conserved at the activity level during the evolution of human populations, thereby avoiding any marked reduction of the activity through a loss of such functional variants, as already demonstrated for other members of the human DNase family: DNase I-like 1 (1L1) 33 , DNase 1L2 29,34 , DNase 1L3 14,16 and DNase II 35 .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…However, all of these functional variants resulting in loss of function, except for SNP p.Arg107Gly with a MAF of 0.004, exhibit a remarkably low distribution (Table 2), similar to that of the CNVs. Thus, it is plausible to assume that DNASE1 has been well conserved at the activity level during the evolution of human populations, thereby avoiding any marked reduction of the activity through a loss of such functional variants, as already demonstrated for other members of the human DNase family: DNase I-like 1 (1L1) 33 , DNase 1L2 29,34 , DNase 1L3 14,16 and DNase II 35 .…”
Section: Resultsmentioning
confidence: 89%
“…In fact, we have demonstrated that the allele producing a low-activity DNase I isoform in common SNP p.Gln244Arg was associated with a higher incidence of MI 12 . Previous studies have demonstrated that the genes encoding members of the human DNase family, DNases 1L1, 1L2, 1L3 and II 14,16,33–35 , exhibit remarkably low genetic heterogeneity with regard to missense SNPs, irrespective of whether or not they affect the respective DNase activity. In contrast, SNPp.Gln244Arg in DNASE1 has a marked effect on the enzyme activity and is distributed worldwide at the polymorphic level.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting its role in muscle tissue, human studies have identified SNPs in DNASE1L1 associated with the development of Pompe's disease (84), which is a metabolic disorder characterized by myopathy, respiratory weakness, physical disability and premature death. However, studies involving larger and more diverse cohorts did not validate these observations (85) and the only SNP in DNASE1L1 that abrogates its endonuclease activity was not associated with Pompe's disease (187). Conversely, a recent analysis suggested that DNASE1L1 SNPs may be linked to type 1 diabetes, schizophrenia and ANCA-associated vasculitis (86).…”
Section: Extracellular Dnases: Key Regulators Of Cfdna-mediated Systementioning
confidence: 99%
“…We have been conducting genetic and expression analyses of nonsynonymous SNPs in the DNase family genes in order to evaluate whether these SNPs may be functionally implicated in various diseases, including autoimmunity (Table 2). Our studies have demonstrated that almost all of the nonsynonymous SNPs in the genes encoding other members of the human DNase family, DNase I-like 1 (Ueki et al, 2010a(Ueki et al, , 2014a, I-like 2 , and I-like 3 (Ueki et al, 2009(Ueki et al, , 2014b, along with DNase II (Ueki et al, 2010b;Kimura-Kataoka et al, 2013), exhibit a mono-allelic distribution in the same study populations, similar to DNase I. These findings enable us to conclude that the human DNase family has, on the whole, been well conserved at the protein level during the evolution of human populations.…”
Section: Discussionmentioning
confidence: 80%